Crime under lockdown: The impact of COVID-19 on citizen security in the city of Buenos Aires - Santiago M. Perez-Vincent; Ernesto Schargrodsky; Mauricio García Mejía (Inter-American Development Bank (IDB), 2021)
This paper studies the impact of the COVID-19 pandemic and the subsequent lockdown on criminal activity in the City of Buenos Aires, Argentina. We find a large, significant, robust, and immediate decline in crime following quarantine restrictions. We observe the effect on property crime reported to official agencies, police arrests, and crime reported in victimization surveys, but not in homicides. The decrease in criminal activity was greater in business and transportation areas, but still large in commercial and residential areas (including informal settlements). After the sharp and immediate fall, crime recovered but, as of November 2020, it did not reach its initial levels. The arrest data additionally allow us to measure the distance from the detainees' address to the crime location. Crime became more local as mobility was restricted.
Keywords: J18; K42; 330; citizen security; crime; Argentina; COVID-19; lockdown